Evaluating the Morphology of Pictographs in Lorestan, Iran Case Study: Dog Motif - sara sadeghi; javanmardzadeh ardeshir; manijeh hadian dehkordi; reza rezaloo (Dānishhā-yi būmī-i Īrān, 2023)
Dogs are one of the first animals domesticated by humans. Dogs have always been a good friend and companion of humans. The paintings found in the caves of primitive humans indicate that the relationship between humans and dogs is at least 16 thousand years old. Dogs are found in different scenes and poses in Iranian rock art in all four cultural regions (i.e., north, west, south, and east). Regarding the history, diversity, and dispersion of the dog motifs in pictographs of different areas in Iran, this study aims to evaluate dog motifs and their breeds in the rock artworks of Lorestan. The main research questions are: "What is the morphology and breed of dog motifs in pictographs of Lorestan?" "Which kind of scenes and subjects are included in pictographs in Lorestan?" and "What rock artworks can be compared to dog motifs in pictographs of Lorestan?" The current study is a qualitative research using a descriptive-analytical-comparative approach. The data was collected by library and field research. The statistical population included Lorestan pictographs in Mehrdad Stone and Mirmalas in Kuhdasht, and Takhte Chan in Poldokhtar. The results showed that dog motifs in pictographs of Lorestan are different in morphology.